ESTIMATION OF THE IMPORTANCE OF BIOLOGICAL VALUE OF NUTRITION ALLOWANCES OF SPORTSMEN OF WEIGHTLIFTING IN THE CONDITIONS OF THE HOT CLIMATE - Tukhtarov B.E; Valiyeva M.U; Khidirov N.Ch (Scholar Express Journals, 2023)
It is established, that equation of nutrition substances in the changed background of a food has reached an optimum level and has made 1:1.1:4.1, against 1:1.2:4.9 on an actual background of a food. The optimality of a parity of nutrition substances in daily average nutrition allowances of sportsmen on the changed background of a nutrition is reached thanks to increase in norms of a food of fibers of an animal origin, vegetative fats and to decrease in sources of carbohydrates. The general biological value of daily average diets on the changed background of a nutrition at sportsmen of weightlifting has raised in an summer-autumnal season has raised to 88.7 1.0 %, with 72.4 1.0 % on an actual background of a food, and in a winter-spring season to 82,8 1.0 %.
Keywords: professional sportsmen; weightlifting; hot climate; food allowances